Among bees, knowledge and protest buzzes - Herrera Jiménez, Marilyn Gabriela (SATHIRI, 2021)
In the nature, there is a delicious natural flavor, “honey”; the work behind the scenes involves a perfectly, coordinated and synchronized production process, It´s not easy, there is an organized family working very hard and every day, each member with a specific responsibility. However, the bees whose integrate it and was consider the most relevant species by the ancient cultures such as Egyptian, Greek, Roman and others, are in danger of extinction due to some factors, the main one “the human activities”. The plant-insect and pollination relationship are fundamental for human permanence, without these elements, food would be scarce, a large part of the delicious fruits and some vegetables that come from a plant that has pollinated would disappear and with it famines would affect everyone. It´s necessary to propose solutions that allow an opportunity for those industrious insects, whose primary function is not to produce honey, the real importance is to pollinate the flowers enabling fertilization and the generation of seeds. Some international organizations have propos initiatives reflected in documents and laws to protect them, however, it´s necessary more interaction, we still have time to save the bees and other kind of species including humans. This research has a qualitative approach and has the objective to show the importance of the bees for the planet.